Design of a Type-1 Diabetes Vaccine Candidate Using Edible Plants Expressing a Major Autoantigen - Bertini, Edoardo; Merlin, Matilde; Gecchele, Elisa; Puggia, Andrea; Brozzetti, Annalisa; Commisso, Mauro; Falorni, Alberto; Bini, Vittorio; Klymyuk, Victor; Pezzotti, Mario; Avesani, Linda (Frontiers in Plant Science, 2018)
Type-1 diabetes (T1D) is a metabolic disease involving the autoimmune destruction of insulin-producing pancreatic beta cells. It is often diagnosed by the detection of autoantibodies, typically those recognizing insulin itself or the 65-kDa isoform of glutamic acid decarboxylase (GAD65). Oral insulin can be used to induce systemic immunological tolerance and thus prevent or delay the onset of T1D, suggesting that combination treatments with other autoantigens such as GAD65 could be even more successful. GAD65 has induced oral tolerance and prevented T1D in preclinical studies but it is difficult to produce in sufficient quantities for clinical testing. Here we combined edible plant systems, namely spinach (Spinacia oleracea cv Industra) and red beet (Beta vulgaris cv Moulin Rouge), with the magnICON expression system to develop a safe, cost-effective and environmentally sustainable platform for the large-scale production of GAD65. The superior red beet platform was extensively characterized in terms of recombinant protein yields and bioequivalence to wild type plants, and the product was tested for its ability to resist simulated gastric digestion. Our results indicate that red beet plants are suitable for the production of a candidate oral vaccine based on GAD65 for the future preclinical and clinical testing of T1D immunotherapy approaches.